Analyzing approaches to learning through the lens of metacognitive awareness and epistemic curiosity - Yazici, Tugce; Kartal, Osman Yilmaz (Asian Journal of Contemporary Education, 2025)
This study investigates the impact of high school students' levels of epistemic curiosity (EC) and metacognitive awareness (MCA) on their learning approaches, aiming to address the achievement gap. The Approaches to Learning Scale, Metacognitive Awareness Inventory, and Epistemic Curiosity Scale were administered to 756 students in the 9th and 12th grades. Using an ex post facto research design, ordinal logistic regression analysis revealed that both interest-type and deprivation-type EC significantly predicted the deep learning approach at both grade levels. While MCA significantly predicted deep learning, the regulation of cognition was not a significant predictor at the 12th-grade level. At both grade levels, deprivation-type EC and cognitive control processes were significant predictors of the strategic learning approach. However, the analyses on the surface learning approach showed that neither EC nor MCA was a significant predictor at either grade level. These findings demonstrate that EC and MCA are critical variables in understanding high school students' learning approaches. The findings indicate that the cultivation of these competencies can facilitate deep and strategic learning while concomitantly reducing achievement gaps. Furthermore, the study emphasizes the necessity for additional research to be conducted on the interaction of these variables across various educational contexts.